Language Use in Multilingual Class: A Case of the English Department Students - Ariana Nur Rohmah; Oluwakemi Dorcas LAWAL (Universitas PGRI Semarang, 2026)
In an Indonesian context, in which linguistic diversity occurs with high intensity, this study examined the use and preferences of languages by multilingual students in an English Department. Based on the definition of multilingualism, this study aims to characterize the languages employed by students in various contexts and explore their preferences for embedded languages within a classroom interaction. Using purposive sampling, 25 sixth-semester students were enrolled in a descriptive survey design. A structured questionnaire was used as a data collection tool, and data were analyzed using percentage-based descriptive statistics. The findings show that, though all participants were multilingual, their use of those languages depended on context. Javanese is used the most at home and in social environments, while Bahasa Indonesia is mainly spoken on campus. Most students would mix up both English and Bahasa Indonesia in classroom context instead of using it fully. The findings also suggest that, based on their perceived limited English proficiency, students favor bilingual ones. They choose foreign languages based on several factors such as language anxiety, willingness to communicate and international posture. This suggests that English departments need to make greater efforts to increase exposure to English and also create environments in which students can use the language more consistently in an academic context.